A simplified model for the post-fire earthquake flexural response of reinforced concrete walls with boundary elements. (15th November 2018) - Ni, Shuna; Birely, Anna C.
Highlights: Simplified nonlinear model for post-fire earthquake response of RC walls is presented. Modification factors are applied to existing models for RC wall response. Modification factors account for the change in stiffness, strength, and deformation. Fire-damage indices (FDI) quantify the residual material properties due to fire. Recommended modification factors are a function of axial load ratio and FDI. Abstract: A potential multi-hazard scenario for buildings is the sequential occurrence of fire and earthquakes, with such a scenario possible if a fire is triggered by an initial seismic event and a subsequent aftershock occurs. With fire negatively influencing the stiffness, strength, and deformation capacity of structural components, the building may be at risk for local or global collapse. The key role of reinforced concrete (RC) walls as lateral load resisting components make them of particular importance in considering the post-fire earthquake performance of buildings. Since the risk of fire-earthquake hazards is low, simplified models are needed to efficiently evaluate building performance. In this paper, a framework for simplified nonlinear modeling of RC walls is presented. The models are defined by modification factors that account for the change in wall response relative to that of a wall without fire damage. Modification factors, established from the results of a parameter study of walls using a verified simulation method, are a function of fire damage indices that account for the effect of fire on the material properties of steel and concrete. The dependence of wall response on most wall characteristics is eliminated by use of the damage indices, with the recommended modification factors dependent on the fire damage index and axial load alone.